AN IMPLEMENTATION OF CARBON EFFICIENT VM PLACEMENT AND MIGRATION TECHNIQUE IN CLOUD ENVIRONMENT (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
Electricity consumption is set to rise 76% from 2007 to 2030 and datacenters are the main contributors of an importantÂ portion of this increase, emphasizes the importance of reducing energy consumption in clouds. Increase in the level ofÂ carbon dioxide in our ecosystem is another consequence of this increasing amount of energy consumption by theÂ datacenters. According to Gartner, the Information and communication industry produces 2% of global carbon dioxideemission [10]. Hence, there is a great requirement of making use of more environmentally friendly computing calledÂ â€œGreen Cloud Computingâ€ to minimize operational and energy consumption costs and also to reduce the environmentalimpact. In this paper, we have implemented the carbon efficient VM placement and migration technique in cloud simÂ simulator.